2021
DOI: 10.1091/mbc.e20-07-0453
|View full text |Cite
|
Sign up to set email alerts
|

Costameric integrin and sarcoglycan protein levels are altered in aDrosophilamodel for Limb-girdle muscular dystrophy type 2H

Abstract: Expression of human disease-causing LGMD2H alleles in Drosophila causes muscle degeneration and elevated levels of integrin and sarcoglycan costamere proteins, likely exacerbating disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Of note, glycogen can contribute to the formation of protein-polysaccharide complexes in muscle. For example, sarcoglycans, linking the actin cytoskeleton with the extracellular matrix to anchor the sarcolemma during muscle contraction, are altered by TRIM32 ablation in both the fruitfly and C2C12 cell models [31,32]. Taken together, these findings indicate that common pathways controlled by malin and TRIM32, even in a contrasting manner, may deserve further investigation to potentially identify novel therapeutic targets for both LD and LGMDR8.…”
Section: Regulation Of Glucose Metabolismmentioning
confidence: 87%
See 1 more Smart Citation
“…Of note, glycogen can contribute to the formation of protein-polysaccharide complexes in muscle. For example, sarcoglycans, linking the actin cytoskeleton with the extracellular matrix to anchor the sarcolemma during muscle contraction, are altered by TRIM32 ablation in both the fruitfly and C2C12 cell models [31,32]. Taken together, these findings indicate that common pathways controlled by malin and TRIM32, even in a contrasting manner, may deserve further investigation to potentially identify novel therapeutic targets for both LD and LGMDR8.…”
Section: Regulation Of Glucose Metabolismmentioning
confidence: 87%
“…Regarding the C-terminal NHL repeats, no structural data is available for either protein, but the high sequence similarity between TRIM32 and malin would suggest that the NHL domain presents a similar three-dimensional structure. The crystal structure of the NHL domain of the TRIM32 Drosophila orthologue, thin, was recently solved and shown to fold in the typical beta-barrel shape (PDB 6D69; 6XG7) [31,32]. Using the Swiss-Model homology modeling software (https://swissmodel.…”
Section: Domain Compositionmentioning
confidence: 99%
“…As with Brat and Lin41, the NHL domain of Mei-P26 and Thin/Abba also exhibit a highly positively charged patch on their top surface (Supplementary Fig. 1D) (3,31,55,56). Because it has been experimentally demonstrated that RNA binding in NHL domains occurs via this charged surface area, it was previously assumed that Mei-P26 NHL can also bind to RNA (3,6,31).…”
Section: Mei-p26 Nhl Binds To Single-stranded Rnamentioning
confidence: 59%
“…We compared the structure of Mei-P26 NHL to the NHL domains of Brat, Lin41 and Thin/Abba to gain further insights into their unique and commonly shared features (3,31,55).…”
Section: Mei-p26 Nhl Binds To Single-stranded Rnamentioning
confidence: 99%
“…Drosophila body wall skeletal muscles have emerged as an important model system to determine the mechanisms of muscle growth and differentiation [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Previously, we have found that FoxO overexpression in larval body wall skeletal muscles leads to myofiber atrophy and reduces developmental muscle growth [35], suggesting that the fruit fly Drosophila melanogaster can be used to identify evolutionary-conserved regulators of myofiber size [10,36,37].…”
Section: Introductionmentioning
confidence: 99%